Studies on the Cd(II) removal from water by adsorption - Singh D.B.; Rupainwar D.C.; Prasad G.; Jayaprakas K.C. (My University, 2025)
The feasibility of using hematite for the removal of Cd(II) from aqueous solutions was investigated employing an adsorption technique. The adsorption was found to depend on Cd(II) concentration, pH, particle size of hematite, agitation rate and temperature of the system. The maximum removal was found to be 98% for the cadmium concentration of 44.88 μmol l-1 at a temperature of 20°C and pH 9.2, with 40 g l-1 of hematite of particle size < 200 μm with agitation 125 rpm rate after 2 h. The applicability of the Langmuir isotherm was tested for the Cd(II)-hematite system at optimum conditions. The process follows first order kinetics. The mass transfer coefficient, diffusion coefficient and thermodynamic parameters have been determined to elucidate the mechanism of uptake. The uptake of cadmium is partially diffusion controlled and partially due to an electrostatic effect along with specific adsorption involving Cd++ and CdOH+ which seem to play an effective role. The data has been subjected to multiple regression analysis and a computer model has been developed to predict the removal of Cd(II) from water under certain boundary conditions. The present technique has been found to be cost-effective.